THE IMPACT OF INTERNATIONAL MIGRATION ON IMMIGRANT’S HOME COUNTRY: EXPLORING DIASPORA POWER AND CONFLICT - Londo, Dennis Lazaro (American Journal of International Relations, 2020)
Purpose: The aim of this study was to explore the effects caused by international migration to the home countries of immigrants. This study also sought to scrutinize the predicaments that face the diaspora in trying to balance their relationships with both the host and home countries. This study suggests that effects of migration on immigrants' home countries can be both positive and negative. Methodology: This study undertook a two dimensional approach whereby a focus was first put on the positive effects and later an overview of negative effects was considered. Analysis was based on systematic literature review on relevant studies that have been conducted within this line of idea. Findings: Developing countries are more negatively affected by migration as compared to developed and industrious countries. Similarly, the study found out that diasporas of third world countries living in developed countries are willing to spend more time in their host countries than returning back home. Unique Contribution to Practice and Policy: This study recommends that governments of developing countries should draft policies that can enable their diasporas to contribute economically without restrictions. Such policies can be subsidies on taxation of diaspora funded projects to encourage diaspora investments.